Implementasi Pemanfaatan Sarana dan Prasarana Gedung Pasar Raya Fase VII di Kota Padang - Zidane Alfarizi; Adil Mubarak (Lembaga Yasin AlSys, 2026)
The revitalization of traditional markets is one of the local government’s efforts to improve the quality of public services and support local economic sustainability, as reflected in the construction of the Pasar Raya Phase VII Building in Padang City as a more decent, safe, and comfortable facility for traders and visitors. This study aimed to analyze the implementation of the utilization of facilities and infrastructure in the Pasar Raya Phase VII Building and to identify the factors that influence it. A qualitative method with a descriptive approach was employed, with data collected through interviews, observations, and document studies, and analyzed through the stages of data reduction, data display, and conclusion drawing. The findings show that the utilization of the facilities and infrastructure of Pasar Raya Phase VII has been implemented but remains suboptimal. Physically, the market facilities support safety, comfort, cleanliness, the efficiency of traders’ activities, the improvement of market image, and the sustainability of the local economy. However, such utilization is still partial due to weak policy communication, limited human and financial resources, inconsistent attitudes of implementers in enforcing regulations, and a bureaucratic structure that is not yet optimal in supervision and socialization. Based on George C. Edward III’s policy implementation theory, these four factors constitute the main obstacles to optimizing the utilization of market facilities and infrastructure. These findings underscore the need to strengthen communication, increase resources, enhance the firmness of implementers, and improve bureaucratic mechanisms so that the management of the Pasar Raya Phase VII Building can operate more effectively and sustainably in supporting the revitalization of traditional markets in Padang City.